Improved Learning Outcomes of Natural Science Lessons Through Google Meet Assisted Project Based Learning (PjBL) Learning Models - Rumyani, Ari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this research was to improve student learning outcomes in science grade V elementary schools with a Google meet assisted Project Based Learning (PjBL) learning model. The research conducted was a Classroom Action Research (PTK) with three cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle the students who completed after carrying out the post test were 74%. In the second cycle students who completed after carrying out the post test were 87%. In the third cycle students who completed after carrying out the post test were 90%. These results indicate that the Project Based Learning (PjBL) learning model can improve student learning outcomes, especially grade V science at SDN 2 Cilongok.